Krétakör Works 2008-2012 (1-22 rész) - Schilling, Árpád (Hungary, 2012)
This four disk DVD offers an overall picture of the works of Krétakör (an alternative Hungarian theater group founded by Árpád Schilling in 1995) between 2008-2012. The recordings include theater performances, educational and community development projects, commercial advertising, social awareness, documentaries, feature films and visual arts installations.